(untitled) (Afrika und Übersee, 2025)
Ndam (Eastern Chadic, ISO [ndm]) displays an array of seven or nine surface vowels. However, the distribution and behavior of these vowels, as evidenced from morphophonemic data, shows that the inventory can be reduced to two basic vowels, /ə/ and /a/, if the operation of two prosodies is also admitted. These prosodies, labialization and palatalization, are distinctive units in the phonology of the language, as well as the two basic vowels; together, they account for the full range of surface vowels and their alternations, as shown in this article. The prosodic analysis, a hallmark of the analysis of Central Chadic languages, provides another example of an Eastern Chadic language which exploits prosodies in its phonology (see Roberts 2009). The article concludes by claiming that Chadic vowel systems are all rectangular, with a fundamental dichotomy between high and non-high vowels. The conclusion also warns of the dangers of confusing the two vowels [ɨ] and [ə] in the transcription of Chadic languages.